Impacts of different pig slurry application methods on soil quality indicators in a maize-soybean cropping sequence in the Sub-humid Pampas of Argentina - Pegoraro, Vanesa Romina; Cazorla, Cristian Roman; Bachmeier, Omar; Baigorria, Tomás; Boccolini, Monica Fabiola; Ortiz, Jimena; Lorenzon, Claudio Antonio; Hang, Susana; Zubillaga, Marta Susana (Islamic Azad University–Isfahan Branch, 2023)
Purpose: In Argentina, pig slurry (PS) is spread in surface with N losses in ammonia form. Different methods to decrease these emissions are available, but there is poor information about their impacts on the soil-plant system. The objective of this study was to compare the effects of different PS application methods on the soil quality in a maize-soybean cropping sequence. Methods: PS application methods were evaluated: acidified (AS), incorporated (IS), surface (SS), mineral fertilization (MF) and control (C). The experimental design was arranged in a randomized block with three replicates. Chemical parameters and microbiological parameters were determined. Also, grain yields and N uptake were measured. Results: IS caused increases in anaerobic nitrogen and basal respiration of soil on soybean. Treatments with PS and/or FM showed lower values in pH than C in both crops, and higher electrical conductivity only in maize. SS treatment showed higher Pe on soybean, indicating a maintenance of the P levels with respect to those in MF and C. The concentration of NO3- increased with MF in both crops. In maize, MF presented similar concentrations to AS and SS. IS increased grain yields of maize by 16 %, whereas SS and AS increased yields of soybean by 112% and 79%, respectively, compared to C. Conclusions: The different PS application methods had similar effects on most of the indicators of soil quality. In maize, IS and AS were more efficient in retaining N within the soil-plant system, whereas, in soybean, the SS led to higher yields.